Work engagement and associated factors among Chinese nurses: a multi-centre cross-sectional study - Yuqi Zhang; Lanjun Zhang; Lu Luo; Yan Li; Yu Sun; Zhimin Dai; Xiaofan Bu; Ting Pan (BMC Nursing)
Abstract Background Nurses are essential to health maintenance. Increased work engagement correlates with enhanced performance, positive emotions and improved health and productivity among employees. However, few studies have focused on the associated factors of work engagement, and the results have been controversial. Identifying these associated factors is important. Objectives This study aimed to estimate the individual contributions of a comprehensive list of factors to work engagement among nurses. Design A multicentre cross-sectional study. Settings and participants A total of 371 nurses were recruited using convenience sampling between June and July 2024 from 22 provinces or autonomous regions in mainland China. Methods A self-reported questionnaire, comprising measurement tools of work engagement, work–family conflict, sense of coherence, career identity and demographic information, was used to collect data anonymously. Bivariate analyses (t-tests/ANOVA for categorical variables; Pearson correlation and partial correlation for continuous variables) were conducted to explore associations between variables and work engagement. Significant variables were then included in a multivariate linear regression model to identify independent predictors. Results Ten factors found significant in the bivariate analysis were included in linear regression model of nurses’ work engagement. One factor, not being a specialist nurse, was significantly and negatively associated with nurses’ work engagement. Nine factors were positively associated with nurses’ work engagement, including senior professional title; working in emergency, gynaecology and obstetrics departments; having a general or satisfied attitude toward the job; sense of coherence; career identity and work–family conflict (p < 0.05). Conclusions Our study reveals that work engagement among nurses depend on 10 factors, including not being a specialist nurse; senior professional title; working in emergency, gynaecology and obstetrics departments; general and satisfied with the job; sense of coherence; career identity and work–family conflict. Engaged nurses tend to be involved, committed and compassionate about their work and believe their efforts are valuable. Future studies may develop interventions to enhance work engagement by targeting these associated factors, which can improve nurse retention. Clinical trial number Not applicable.